If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -26 = 18 Reorder the terms: -26 + 4x = 18 Solving -26 + 4x = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '26' to each side of the equation. -26 + 26 + 4x = 18 + 26 Combine like terms: -26 + 26 = 0 0 + 4x = 18 + 26 4x = 18 + 26 Combine like terms: 18 + 26 = 44 4x = 44 Divide each side by '4'. x = 11 Simplifying x = 11
| w^2-11w-42=0 | | X+41/4=331/3 | | 11x-12=-34 | | 2-4/5-6=a | | 5/8=x/20 | | 2-4/5-6= | | 4k-2=11 | | x/3-4=11 | | (a*3)-1=2(a-8) | | .5(x(x-4))=24 | | 3x=23+x | | 5x+53=10x-12 | | y+32=y+16 | | 3x+3=23+x | | 3.2x=8 | | 4(2x+7)-5=39 | | (4x-1)(x+3)=0 | | 3(3x-4)-x=-4 | | x(1-5x)=0 | | x/5-5=2 | | 151-2x=34x+19 | | 12x-27=9 | | 11x+30=90 | | 5x-2/x-3=0 | | 7a= | | 9-10x=144-45x | | (5x+9)-(3X-13)=2(11+x) | | (4x-4)-8=-(3x-2) | | 3(3x+4)=48+6x | | 5x-17=3x+35 | | x^2+.5x-.394=0 | | x^2-635=0 |